The Relationship Between Knowledge and Attitudes of Malaysian Undergraduate Students Towards Dementia - Hussein, Siti Zuhaida; Ismail, Azera Hasra; Zulkefle, Muhammad Fidaus; Azhar, Ahmad Nur Iman; Mahiran, Nurmahirah (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Providing care for vulnerable people, including older adults with dementia, that is safe and efficient is a significant factor in improving their health. This study aims to determine the knowledge and attitudes of undergraduate nursing students regarding dementia in older adults. Methods: This is a cross-sectional study conducted among 126 undergraduate students at a Malaysian university using purposive sampling. The respondents’ knowledge of dementia was measured using the Alzheimer’s Disease Knowledge Scale (ADKS), and their attitudes towards dementia were measured using the Adolescent Attitudes towards Dementia. The scale of P<0.05 was statistically significant, and the data was analyzed using the Statistical Package for the Social Sciences (SPSS) Statistics 26.0 for Windows. Results: The results showed that 78.6% of undergraduate nursing students had higher knowledge of dementia than 92.9% had positive attitudes toward dementia. There is a significant relationship between years of study and knowledge of dementia among UKM nursing students (χ2= 14.93, p = 0.001). Conclusion: Most undergraduate students have higher knowledge of and positive attitudes towards dementia. A better understanding of the disease process improves the quality of life for people with dementia and their caregivers. Longitudinal and comparative studies were suggested for further research.